2016
DOI: 10.1038/mi.2015.69
|View full text |Cite
|
Sign up to set email alerts
|

CD161intCD8+ T cells: a novel population of highly functional, memory CD8+ T cells enriched within the gut

Abstract: The C-type lectin-like receptor CD161 is expressed on lymphocytes found in human gut and liver, as well as blood, especially Natural Killer cells, T helper 17 cells and a population of unconventional T cells known as Mucosal Associated Invariant T (MAIT) cells. The association of high CD161 expression with innate T cell populations including MAIT cells is established. Here we show that CD161 is also expressed, at intermediate levels, on a prominent subset of polyclonal CD8+ T cells, including anti-viral popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
125
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(141 citation statements)
references
References 50 publications
16
125
0
Order By: Relevance
“…Resting CD161++ CD8+ T‐cells, in particular the MAIT cells, express no GrB and little perforin, and instead are uniquely enriched for GrK expression 90. In turn, CD161+ CD8+ T‐cells are enriched for GrB and perforin expression, even compared with their CD161− CD8+ T‐cell counterparts 16. The GrK+ GrB− perforin low phenotype of CD161++ CD8+ T‐cells was similar to the phenotype of CD56 bright NK cells (Fig.…”
Section: Functional Similarities Between Nk Cell and Cd8+ T‐cell Subsetsmentioning
confidence: 75%
See 2 more Smart Citations
“…Resting CD161++ CD8+ T‐cells, in particular the MAIT cells, express no GrB and little perforin, and instead are uniquely enriched for GrK expression 90. In turn, CD161+ CD8+ T‐cells are enriched for GrB and perforin expression, even compared with their CD161− CD8+ T‐cell counterparts 16. The GrK+ GrB− perforin low phenotype of CD161++ CD8+ T‐cells was similar to the phenotype of CD56 bright NK cells (Fig.…”
Section: Functional Similarities Between Nk Cell and Cd8+ T‐cell Subsetsmentioning
confidence: 75%
“…Thus, both CD56 dim NK cells and CD161+ CD8+ T‐cells are enriched for Eomes+T‐bet high cells,16, 107 while CD56 bright NK cells have an Eomes+T‐bet low phenotype,107 which is mirrored by CD8+ MAIT cells 108. Of note, CD161+ CD8+ T‐cells express higher levels of GrB and perforin even compared with their CD161− CD8+ T‐cell counterparts, although both populations contain similar frequencies of effector memory T‐cells and terminally differentiated CD8+ T‐cells 16…”
Section: Functional Similarities Between Nk Cell and Cd8+ T‐cell Subsetsmentioning
confidence: 98%
See 1 more Smart Citation
“…74 In addition, xenobiotic resistance of mucosal-associated invariant T cells (MAIT) CD8 + T cells (TCR Vα7.2 + ) has been associated to their MDR1 expression. These MAIT also express high levels of CD161 and secrete IL-17A or both IFN-γ and IL-17A, displaying Tc17 and Tc1.17-like phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are at least two distinct populations of CD8 + T lymphocytes: cytotoxic T lymphocytes (CTL) that respond to viral peptide presentation (Zhang and Bevan 2011) and MAIT cells that respond predominately to bacteria (Chen et al 2017;Dusseaux et al 2011;Gold et al 2010). It has been shown that ~10% of CD8 + lymphocytes have now been identified as MAIT cells by virtue of Vα7.2 and CD161 hi expression (Cosgrove et al 2013;Dusseaux et al 2011;Fergusson et al 2016;Walker et al 2012). This calls into question previous work that has failed to exclude Vα7.2 + CD161 + cells from their CTL analysis.…”
Section: Cd8mentioning
confidence: 99%